Kultura castro oraz procesy celtyzacji i romanizacji na terenie Galicii w Hiszpanii - Kmieciński, Jerzy; Kowalczyk, Małgorzata (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The Castro Culture occupies the area of northern-western part of Pyrenees (Galicia, the northern part of Portugal). Chronological limits according to the contemporary investigations are said to be from the 6th century В. C. till the end of the 1st century A. D., however some researchers claim that some significant elements of this culture lasted till the end of the 6th century A. D. The name of this culture as the archaeological notions was adopted in the 19th century and was specified by P. Bosch-Gimpera in 1932. Due to the existence of defensive settlements (castra) it was supposed that this culture was of Celtic origin. The eastern Trans-Pyrenees province of Galicians was also mentioned. Whereas, the notions Celtos and Castros were treated as synonyms (Jose Vera у Aguiar). The function of castra was differently interpreted either as tombs, sanctuaries or fortifications built in protection of tracks. Castra were also treated as areas with organized settlement (Murguia). Due to significant archaeological discoveries made in the end of the 19th century some very explicit cultural features of the regions occupied by defensive settlements of castro types are more clearly seen. Two main architectonic forms appearing in castra - i. e. buildings of ovate and orographic projection constructed of cast wall are distinguished. Specific style of decoration of pottery by means of die ornament was also notified. As compared to the rest of Iberian territory the specific jewelery, especially fibulas, torkwes, bracelets and earings were distinguished.